Leadership matters: A conversation with Dr. James Hildreth - Jason Wolf (The Beryl Institute, 2020)
I was extremely honored at this moment in the midst of our current health crisis to have a conversation with Dr. James Hildreth, president and chief executive officer of Meharry Medical College. The focus and commitment expressed by Dr. Hildreth reflects the very mission statement of Meharry Medical College itself, to advance health equity through innovative research, transformative education, exceptional and compassionate health services and policy-influencing thought leadership. As equally important is the alignment of Meharry's purpose with our very own at the Institute, as Meharry's mission continues to empower diverse populations to improve the well-being of humankind. Dr. Hildreth challenges us to find common context, follow the science and recognize that leadership matters. He calls on us to stop making assumptions and find a place of understanding, acknowledgment and action. Experience Framework This article is associated with the Culture & Leadership lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Culture%20%26%20Leadership%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens